Nanotecnologia e meio ambiente para uma sociedade sustentável - Paulo Martins (Estudios Sociales)
This paper has seven topics that discuss the relationship between Nanotechnology and Environment to build a Sustainable Society. In a glance is showed what is nanotechnology and its recent history (topics 1 and 2). In continuity is presented the theoretical bases to understand the relationship between environment and technological opportunities. The topic4 introduce nanotechnology in the reflection about environment and technological opportunities. Nanotechnology and Sustainable is discussed in the topic 5. After theses previews topic are presented the preliminary conclusions and suggestions to the theoretical reflections.